(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
In recent decades, there has been a sharp increase in waste that pollutes the environment. It can be categorically stated that non-degradable waste has the largest share in them. They are most easily discharged and condensed in water bodies on land, and subsequently in the world's oceans. Still, measures are usually taken after floods or other emergencies occur. Not enough preventive measures are being taken. The report proposes a model for monitoring and recording unregulated dumping in and around mainland water bodies. The aim of the research is to develop a system for monitoring pollution in and around water bodies, transmitting this information, analyzing it and making decisions about the removal of pollutants. As a secondary goal, a preventive measure to limit pollution can also be indicated, because when there is control and subsequent punishments, the violations also decrease to a significant extent. A review was also made of good practices in the collection of waste in water bodies. A system for collecting information and removing the accumulated waste is proposed. It is also proposed to implement a method put in place last year in Australia to collect waste in running water. A mobile version will also be developed to signal the presence of waste, when every citizen will be able to signal the presence of such unregulated pollution. You will also use your knowledge after equipping the astronomy club to observe space debris and to create floating island fruits from the plastic waste in the world's oceans. In addition, technologies are used that are innovative and have the potential to solve these global problems. In carrying out the research, various methods were used - analysis, data synthesis, data processing and others.